ImmunoFacts : (Facts and Comparisons, 2002)
Comprehensive collection of immunologic and vaccine information. Provides comparative tables, international travel and catch-up schedules for childhood immunizations, dosing considerations for adults and children, international trade name listings, vaccine excipient, and media summary.